Improving the irradiation resistance of inverted flexible 3J solar cells by adjusting the structure. (1st January 2023) - Wang, Xin; Li, Bin; Zhou, Lihua; Shi, Xianglei; Sun, Lijie; Wang, Xunchun
Highlights: We analyze the degradation behavior and current limiting unit of GaInP/GaAs/InGaAs triple-junction inverted metamorphic (IMM3J) solar cells under 1Mev electron irradiation. We have improved the irradiation resistance of the IMM3J cell by optimizing the back surface field of the top-cell and bandgap of sub-cell on the basic IMM 3J solar structure. We characterized the anti-radiation capability of different structure cells by calculating the minority carrier decay coefficient on reasonable assumption and derivation. Abstract: Highly efficient, flexible, and lightweight thin-film solar cells play an important role in the aerospace field. To improve the radiation resistance of GaInP/GaAs/InGaAs triple-junction inverted metamorphic (IMM3J) solar cells under intense electron irradiation in space, the back field of the top cell and band gap of the middle cell were optimized. Under 1 × 10 15 e/cm 2 electron irradiation, compared with the reference cell, the attenuation of the conversion efficiency of the backfield-optimized cell and bandgap-adjusted cell was reduced by 10.3 % and 2.8 %, respectively. According to the spectral response and electrical properties, the current-limiting units of the different cells before and after irradiation were analyzed. The increase in the aluminum (Al) component increased the barrier of the AGaInP back surface field, promoted the carrier absorption of the top cell, and increased the initial current of the solar cell. Optimization of the bandgap in the middle cell enables the bottom cell with a redundant current to resist irradiation attenuation. Both adjustments optimize the current-matching relationship between the sub-cells after irradiation. The decay coefficient of the minority carrier was calculated using the electrical displacement damage theory, and the lifetime decay coefficient of the minority carrier was further estimated, which indicated that the radiation resistance was improved. In addition, the mechanism of improving the radiation resistance is discussed in detail by the characteristics of carrier transport, which provides an optimal direction for improving the irradiation characteristics of solar cells in the future.